Fuel cell for converting methane into low-carbon hydrocarbon and related method

By using ceramic materials and oxygen-ion-electron hybrid conductor materials and methane oxidation coupling catalysts in solid oxide fuel cells, the problem of high cost and safety hazards of methane oxidation coupling technology is solved, and the direct result from methane to low-carbon hydrocarbons is realized Conversion and electricity generation improve conversion rate and selectivity.

CN119133467APending Publication Date: 2024-12-13PETROCHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310696990.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing methane oxidation coupling technology is costly and has safety risks. Traditional solid oxide fuel cells are not suitable for hydrocarbon fuels, and it is difficult to achieve direct conversion of high-value-added olefin products.

Method used

A ceramic material is used to replace the metal material in the anode material of the traditional fuel cell, and combined with an oxygen-ion-electron hybrid conductor material and a methane oxidation coupling catalyst to design an oxygen-containing cathode material flow at high temperatures. The process is separated from the methane-containing anode stream to avoid direct mixing, achieving direct conversion of methane to low-carbon hydrocarbons and generating electrical energy.

Benefits of technology

It reduces operating costs, improves safety, enhances selectivity to ethylene, inhibits the occurrence of carbon deposits and side reactions, improves methane conversion and product selectivity, reduces membrane area or increases oxygen supply rate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a fuel cell for converting methane into low-carbon hydrocarbon and a related method. The anode material of the fuel cell comprises a methane oxidative coupling catalyst and an oxygen ion-electron mixed conductor material; the fuel cell is used for converting methane into low-carbon hydrocarbon and generating electric energy in a working state that a cathode feed flow is a first mixed gas containing oxygen and an anode feed flow is a second mixed gas containing methane. According to the fuel cell, a metal material in a traditional fuel cell anode material is replaced by a ceramic material, so that carbon deposition is inhibited; on the basis, the catalyst is combined with a methane oxidative coupling catalyst, so that direct conversion from methane to low-carbon hydrocarbon is realized in the SOFC, and electric energy is generated at the same time; and the problems of high cost and potential safety hazards of the existing methane oxidative coupling technology are also solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of natural gas conversion and utilization, and in particular to a fuel cell for converting methane into low-carbon hydrocarbons and a related method. Background Art

[0002] As the main component of natural gas, methane is the smallest and most stable molecule among hydrocarbons. Due to its high carbon-hydrogen bond energy, low activity, and difficulty in processing and utilization, it is difficult to directly use as a chemical raw material compared to other higher molecular weight hydrocarbons. Ethylene and ethane are both important basic chemical raw materials, especially ethylene. At present, my country's ethylene raw materials are still mainly crude oil, and the cost of ethylene is greatly affected by crude oil price fluctuations. Therefore, new ways to prepare ethylene using other raw materials have received increasing attention in recent years. With the large-scale discovery and exploitation of methane-rich shale gas, natural gas hydrates, biogas, etc. around the world, replacing oil with relatively abundant and low-priced natural gas to produce basic chemicals such as ethylene has become the focus of research and development in academia and industry.

[0003] In the industrial technology that has been widely used, the conversion and utilization process of natural gas mainly includes two steps: first, by mixing carbon dioxide or water vapor, the methane molecules in the natural gas are reformed at high temperature into synthesis gas containing a specific carbon monoxide / hydrogen ratio. Subsequently, the synthesis gas is converted into high-carbon hydrocarbon molecules (oil products and basic chemicals, etc.) under the action of a specific catalyst by Fischer-Tropsch synthesis (FT synthesis); or the synthesis gas is first converted into methanol, and then dehydrated by a microporous molecular sieve catalyst, and then olefins and other chemicals are produced from methanol. The above-mentioned traditional methane conversion path is lengthy, with high equipment investment and energy consumption, and a large amount of carbon dioxide greenhouse gas is inevitably formed and emitted in the process, which affects the ecological environment on the one hand and greatly reduces the utilization rate of total carbon on the other hand. Therefore, it is of great significance to develop an effective path for the direct conversion and utilization of natural gas.

[0004] Patent CN 1266041A discloses a route for catalytic conversion of methane by methane aromatization reaction under oxygen-free conditions. This route uses Mo / HZSM-5 as a catalyst, and converts methane into benzene, toluene and naphthalene, and releases hydrogen under the conditions of reaction temperature of 600-750°C and reaction pressure of 2 bar at normal pressure. However, due to the high specific surface area of ​​the catalyst and the reaction in an oxygen-free environment, this route is usually accompanied by the formation of by-product carbon deposition and rapid catalyst deactivation.

[0005] Patent US 20150087875A1 discloses a methane oxidative coupling catalyst for catalytically converting methane to produce dicarbon aliphatic hydrocarbons under aerobic conditions. The catalyst is prepared using nanotechnology and has a nanowire morphology. Under reaction conditions of 550°C and 2 bar, the catalyst catalytically converts methane into dicarbon and multicarbon aliphatic hydrocarbons, with a yield of aliphatic hydrocarbons greater than 5%. However, the dicarbon aliphatic hydrocarbons in the product are mainly ethane, and the added value is not as high as ethylene.

[0006] Patent CN1389293A discloses a catalyst for the production of ethylene by pressurized oxidative coupling of methane. The catalyst uses silicon dioxide as a carrier, and the active components are composed of SnO2, Mn2O3 and Na2WO4. Under the conditions of a reaction temperature of 750-800°C and a reaction pressure of 0.6MPa, the yield of C2+ products is improved. Since the reaction requires pressurized conditions, the risk of explosion is increased, and there are potential safety hazards.

[0007] Patent CN1072615A discloses a methane oxidative coupling catalyst prepared from alkaline earth metal oxides and alkaline earth metal carbonates. Under conditions of 550°C to 850°C and normal pressure, the yield of aliphatic hydrocarbons is 20%. Summary of the invention

[0008] The inventors found that for the above patented technologies for methane oxidative coupling, the design of the reaction process all uses conventional fixed bed or fluidized bed reactors, and directly uses a certain proportion of methane and pure oxygen mixture as the feed stream. The supply of pure oxygen requires the addition of an air pre-separation device, which increases operating costs; at the same time, methane and pure oxygen are directly mixed and introduced into a high-temperature environment. If the operation is improper, it will cause the risk of explosion and pose a safety hazard. Therefore, the process design of the methane oxidative coupling reaction still needs to be improved.

[0009] The inventors also found that the anode material of the traditional solid oxide fuel cell (SOFC) is mainly a composite material of metal (such as Ni, Pt, etc.) and oxygen-conducting ceramic (such as YSZ, GDC, etc.), and the applicable fuel is mainly hydrogen or synthesis gas. This anode material is not suitable for hydrocarbon fuels because the metal materials such as Ni in the anode will cause serious carbon deposition during the reaction, causing the battery performance to decline rapidly.

[0010] Patent CN1268255A describes a method for activating and utilizing methane using a solid oxide fuel cell. The method uses methane as fuel and reacts it with oxygen to produce products such as water, carbon dioxide, carbon monoxide and hydrogen and generate electricity. However, the patent is mainly used in the field of power supply, and the products obtained by the reaction are mainly carbon oxides, etc., and the added value of the products is very low.

[0011] Patent CN100595952C describes a method for improving the efficiency of methane reaction by combining a solid oxide fuel cell with a methane water gas reforming catalyst. By combining the water gas reforming catalyst with the anode of the fuel cell, the anode's anti-carbon deposition performance is significantly improved, and the battery power density is also significantly improved. Although this patent combines the catalytic reaction with the fuel cell, it still focuses on power generation and cannot produce high value-added olefin products.

[0012] Patent CN 109385643 A discloses a fuel cell device for converting methane into aliphatic hydrocarbons and a preparation method thereof. The disclosed fuel cell structure includes a cathode, a cathode transition layer, an electrolyte and an anode. The anode is composed of a methane oxidative coupling catalyst and an inert conductive metal material, the electrolyte is an oxygen ion conductor ceramic material, and the cathode transition layer is a mixture of the cathode and electrolyte materials. The anode structure uses gold or copper, which is relatively expensive on the one hand and does not have ion conductivity on the other hand, which limits the three-phase interface area of ​​methane conversion.

[0013] In view of the problems that the methane oxidative coupling patent technology in the prior art is high in cost and has great safety hazards, and traditional solid oxide fuel cells are not suitable for hydrocarbon fuels, in order to at least partially solve the technical problems existing in the prior art, the inventors have made the present invention, and through specific implementation methods, provide a fuel cell and related methods for converting methane into low-carbon hydrocarbons.

[0014] In a first aspect, an embodiment of the present invention provides a fuel cell for converting methane into low-carbon hydrocarbons, wherein the anode material of the fuel cell includes a methane oxidative coupling catalyst and an oxygen ion-electron mixed conductor material;

[0015] The fuel cell is used to convert methane into low-carbon hydrocarbons and generate electrical energy when the cathode feed stream is a first mixed gas containing oxygen and the anode feed stream is a second mixed gas containing methane.

[0016] In a second aspect, an embodiment of the present invention provides a method for converting methane into light hydrocarbons, comprising:

[0017] A first mixed gas containing oxygen is introduced into the cathode of the fuel cell, and a second mixed gas containing methane is introduced into the anode of the fuel cell. The fuel cell converts the methane in the second mixed gas into low-carbon hydrocarbons to generate electrical energy.

[0018] The beneficial effects of the above technical solution provided by the embodiment of the present invention include at least:

[0019] (1) The fuel cell provided by the embodiment of the present invention uses ceramic materials to replace the metal materials in the anode materials of traditional fuel cells, which can inhibit carbon deposition and avoid the problem of limited three-phase interface area for methane conversion in fuel cells using metal anode materials; on this basis, it is combined with a methane oxidative coupling catalyst to achieve direct conversion of methane to low-carbon hydrocarbons in SOFC and generate electricity at the same time. It has the advantages of low operating cost, good safety, and high selectivity for ethylene.

[0020] (2) The fuel cell provided in the embodiment of the present invention is an oxygen ion conductor fuel cell, which can highly selectively reduce the oxygen in the oxygen-containing feed stream (first mixed gas) into oxygen ions in situ during the reaction process and provide them to the reaction system, thereby solving the need for an air pre-separation device in the traditional oxidative coupling reaction.

[0021] (3) The fuel cell provided in the embodiment of the present invention has an integrated fuel cell that effectively avoids direct mixing between the methane-containing feed stream and the oxygen-containing feed stream, thereby improving the safety of the reaction.

[0022] (4) The fuel cell provided in the embodiment of the present invention has a special component in the anode, that is, a catalyst having catalytic activity for methane oxidative coupling is compounded with an oxygen ion-electron mixed conductor material. While catalytically converting methane, the occurrence of side reactions such as methane thermal cracking (producing carbon deposits) and water gas reforming is suppressed, thereby improving the selectivity of hydrocarbon products.

[0023] (5) Compared with conventional oxygen permeable membranes, the fuel cell provided by the embodiments of the present invention achieves better in-situ selective oxygen supply effect. Therefore, under a given oxygen supply amount, the required membrane area can be reduced, or a faster oxygen supply rate can be provided under a given membrane area, which is beneficial to improving the methane conversion rate per unit time.

[0024] (6) The anode of ordinary SOFC is Ni / YSZ material, which usually requires a higher sintering temperature (>1400℃) to ensure a good anode / electrolyte interface. At this temperature, the cathode material often loses its microporous structure, thus affecting performance. Therefore, the production of battery cells usually requires step-by-step sintering, that is, the anode is first sintered at high temperature, the cathode is coated after annealing, and then sintered again at about 1200℃. In the fuel cell provided by the embodiment of the present invention, the oxygen ion-electron mixed conductor material comprises a first component and a second component, the first component is a mixture of one or more of LSM, LSCF and LSCM, and the second component is a mixture of one or more of YSZ, ScSZ and GDC; the cathode material of the fuel cell is a mixture of one or more of LSM, LSCF or LSCM. The composite anode material is similar to the cathode material used in the fuel cell in terms of components. In the process of preparing the battery cell, the cathode and anode can be coated at the same time, and then sintered in a high temperature environment (e.g., 1100℃~1200℃) at one time, which improves the battery yield and reduces the energy consumption of the battery manufacturing process.

[0025] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures specifically pointed out in the written description and claims.

[0026] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0027] The exemplary embodiments of the present disclosure will be described in more detail below. It should be understood that the exemplary embodiments of the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0028] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art to which the invention belongs. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0030] In the description of the present invention, it should be noted that the terms "include", "including", "have", "contain" and the like are open terms, meaning including but not limited to.

[0031] In order to solve the problems of high cost and potential safety hazards of methane oxidative coupling in the prior art, the embodiments of the present invention provide a fuel cell and related methods for converting methane into low-carbon hydrocarbons, in which ceramic materials are used to replace the metal materials in the anode materials of traditional fuel cells to inhibit carbon deposition; on this basis, oxygen ion-electron mixed conductor materials are combined with methane oxidative coupling catalysts to achieve direct conversion of methane to low-carbon hydrocarbons in SOFC and generate electrical energy at the same time; at the same time, the problems of high cost and potential safety hazards of existing methane oxidative coupling technologies are solved.

[0032] Example 1

[0033] Embodiment 1 of the present invention provides a fuel cell for converting methane into low-carbon hydrocarbons, wherein the anode material thereof includes a methane oxidative coupling catalyst and an oxygen ion-electron mixed conductor material; the fuel cell is used to convert methane into low-carbon hydrocarbons and generate electrical energy when the cathode feed flow is a first mixed gas containing oxygen and the anode feed flow is a second mixed gas containing methane.

[0034] A solid oxide fuel cell is established. An oxygen-containing feed stream is blown through the cathode of the fuel cell to generate an electrochemical reaction to generate oxygen ions. The oxygen ions move through the electrolyte to the composite anode of the fuel cell. The composite anode contains an oxygen ion-electron mixed conductor material and a methane oxidative coupling catalyst. When the methane-containing feed stream blows through the anode of the fuel cell, methane undergoes a coupling reaction under the action of the oxygen ions and the methane oxidative coupling catalyst to generate low-carbon hydrocarbons and generate electrical energy at the same time.

[0035] Ceramic materials are used to replace metal materials in traditional anode materials to inhibit carbon deposition; on this basis, they are combined with methane oxidative coupling catalysts to achieve direct conversion of methane to low-carbon hydrocarbons in SOFC and generate electricity at the same time. It has the advantages of low operating cost, good safety, and high selectivity for ethylene.

[0036] The fuel cell is an oxygen ion conductor fuel cell, which can highly selectively reduce oxygen in the oxygen-containing feed stream (first mixed gas) into oxygen ions in situ during the reaction process and provide them to the reaction system, thus solving the need for air pre-separation equipment in traditional oxidative coupling reactions.

[0037] The integration of the fuel cell effectively avoids direct mixing between the methane-containing feed stream and the oxygen-containing feed stream, thereby improving the safety of the reaction.

[0038] The anode uses special components, that is, a catalyst with methane oxidative coupling catalytic activity is combined with an oxygen ion-electron mixed conductor material. While catalytically converting methane, it inhibits the occurrence of side reactions such as methane thermal cracking (producing carbon deposits) and water gas reforming, thereby improving the selectivity of hydrocarbon products.

[0039] Compared with conventional oxygen permeable membranes, the fuel cell provided by the embodiment of the present invention achieves better in-situ selective oxygen supply effect. Therefore, under a given oxygen supply amount, the required membrane area can be reduced, or a faster oxygen supply rate can be provided under a given membrane area, which is beneficial to improving the methane conversion rate per unit time.

[0040] The oxygen ion-electron mixed conductor material in the fuel cell anode material comprises a first component and a second component. The first component is (La 0.80 Sr 0.20 ) 0.95 MnO 3-x (LSM), (La 0.60 Sr 0.40 ) 0.95 Co 0.20 Fe 0.80 O 3-x (LSCF) and La 0.75 Sr 0.25 Cr 0.5 Mn 0.5 O 3-x (LSCM), x represents the presence of oxygen vacancies. The material has oxygen vacancies, so it can conduct oxygen ions at high temperatures; the second component is a mixture of one or more of yttrium stabilized zirconia (YSZ), scandium stabilized zirconia (ScSZ) and gadolinium-doped cerium oxide (GDC).

[0041] In the mixed conductor material, the mass fraction of the first component is 10 to 90%, and the mass fraction of the second component is 10 to 90%.

[0042] Preferably, the mass fraction of the first component in the mixed conductor material is 20-80%, and the mass fraction of the second component is 20-80%.

[0043] In some embodiments, the cathode material of the fuel cell is a mixture of one or more of LSM, LSCF, or LSCM.

[0044] The anode of ordinary SOFC is Ni / YSZ material, which usually requires a higher sintering temperature (>1400℃) to ensure a good anode / electrolyte interface, and at this temperature, the cathode material often loses its microscopic porous structure, thus affecting performance. Therefore, the production of battery cells usually requires step-by-step sintering, that is, the anode is first sintered at high temperature, the cathode is coated after annealing, and sintered again at about 1200℃. The fuel cell provided by the embodiment of the present invention, the oxygen ion-electron mixed conductor material comprises a first component and a second component, the first component is a mixture of one or more of LSM, LSCF and LSCM, and the second component is a mixture of one or more of YSZ, ScSZ and GDC; the cathode material of the fuel cell is a mixture of one or more of LSM, LSCF or LSCM. The composite anode material is similar to the cathode material used in the fuel cell in terms of components. In the process of preparing the battery cell, the cathode and anode can be coated at the same time, and then sintered in a high temperature environment (e.g., 1100℃-1200℃) at one time, which improves the yield rate of the battery and reduces the energy consumption of the battery manufacturing process.

[0045] In some embodiments, the electrolyte material of the fuel cell is a mixture of one or more of YSZ, ScSZ and GDC.

[0046] In some embodiments, the anode material of the fuel cell is prepared by solution impregnation.

[0047] Specifically, the precursor of the methane oxidative coupling catalyst is loaded on the powder of the second component and then mixed with the powder of the first component to prepare the anode material.

[0048] The methane oxidative coupling catalyst in the fuel cell anode material is a cerium-manganese-tungsten catalyst, and the cerium-manganese-tungsten catalyst is a mixture of CeO2, Mn2O3 and Na2WO4.

[0049] Furthermore, in the cerium-manganese-tungsten catalyst, the mass fraction of CeO2 is 0% to 50%, the mass fraction of Mn2O3 is 10% to 40%, and the mass fraction of Na2WO4 is 30% to 70%.

[0050] The mass ratio of methane oxidative coupling catalyst and oxygen ion-electron mixed conductor material in the fuel cell anode material is 5:95 to 30:70.

[0051] Preferably, the mass ratio of the methane oxidative coupling catalyst to the oxygen ion-electron mixed conductor material is 12:88 to 27:73.

[0052] The material flow of the cathode of the fuel cell, that is, the molar percentage of oxygen in the first mixed gas is not less than 15%, and the balance gas is nitrogen. Preferably, the material flow of the cathode is air.

[0053] The molar percentage of methane in the material flow of the fuel cell anode, that is, the second mixed gas, is 20% to 80%, and the balance gas is nitrogen.

[0054] The operating temperature of the fuel cell is 600-1000° C. Preferably, the operating temperature is 800-900° C.

[0055] Based on the inventive concept of the present invention, an embodiment of the present invention further provides a method for converting methane into light hydrocarbons, comprising:

[0056] A first mixed gas containing oxygen is introduced into the cathode of the fuel cell, and a second mixed gas containing methane is introduced into the anode of the fuel cell. The methane in the second mixed gas is converted into low-carbon hydrocarbons through the fuel cell to generate electrical energy.

[0057] The preparation process of the above solid oxide fuel cell is common professional knowledge. If not otherwise specified, the prepared cathode and anode materials are coated on both sides of the electrolyte sheet by screen printing, and sintered at 1175°C for 2 hours. The electrode thickness is 10μm-100μm. Gold glue and gold wire are used to measure the current collection and electrical properties.

[0058] The catalytic reaction products were detected by online gas chromatography to calculate the conversion rate, product selectivity, etc. The fuel cell performance was evaluated by linear voltammetry and electrochemical impedance spectroscopy.

[0059] Methane conversion rate (%) = (C 2+ Carbon content of hydrocarbons + carbon content of CO + carbon content of CO2) / total carbon content of gas phase products*100%, where carbon content refers to the molar number of carbon atoms in the compound;

[0060] Hydrocarbon selectivity (%) = hydrocarbon carbon content / total carbon content of gas phase products*100%.

[0061] Example 2: Preparation of LSM / YSZ composite anode material

[0062] Weigh 8.208g Mn(NO3)2·4H2O, 5.058g Na2WO4·2H2O, 13.95g Ce(NO3)3·6H2O and dissolve them in 150mL deionized water, and add 19.2g YSZ powder under stirring. After continuous stirring and impregnation at room temperature for 6 hours, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6 hours. Then grind and sieve to less than 325 mesh to obtain a solid powder. Weigh 5g of the above powder, 5g LSM powder (<325 mesh) and 10g V-006A solvent (the solvent required for making electrode materials, purchased from Heraeus), mix them evenly in an agate mortar to obtain an LSM / YSZ composite anode material. The composition of the anode material is 8.7% CeO2-4.1% Mn2O3-7.1% Na2WO4-30.1% YSZ-50% LSM.

[0063] Example 3: Preparation of LSCF / GDC composite anode material (partial impregnation first, then mixing ceramic solid materials)

[0064] Weigh 1.39g Mn(NO3)2·4H2O, 0.843g Na2WO4·2H2O, 2.33g Ce(NO3)3·6H2O and dissolve in 50mL deionized water, and add 3.2g GDC powder under stirring. After continuous stirring and impregnation at room temperature for 6 hours, slowly concentrate at 80°C until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850°C and sintered in air for 6 hours. Then grind and sieve to less than 325 mesh to obtain a solid powder. Weigh 3g of the above powder, 7g LSCF powder (<325 mesh) and 10g V-006A solvent, mix evenly in an agate mortar to obtain a LSCF / GDC composite anode material. The composition of the anode material is 5.2% CeO2-2.5% Mn2O3-4.2% Na2WO4-18.1% GDC-70% LSCF.

[0065] Example 4

[0066] The LSM / YSZ composite anode material in Example 2 was used to construct a button cell and a fuel cell stack, respectively, and their methane oxidative coupling reaction performance was investigated.

[0067] The button cell test temperature is 900°C, the anode feed is 20% CH4-80% N2, the flow rate is 50mL / min, and the cathode feed is air, the flow rate is 500mL / min. When the output power is 0.04W, the methane conversion rate is 20.1%, the ethylene selectivity is 30.8%, the ethane selectivity is 6.9%, and the remaining products are CO or CO2.

[0068] The fuel cell stack is a dual-cell stack, the electrolyte material is YSZ, and the cathode material is LSM. The total area of ​​a single cell is 81cm 2 , the effective current collecting area is 25cm 2 The test temperature was 800°C and the pressure was 1 atm. The anode feed was methane 100 mL / min, nitrogen 200 mL / min, and the cathode feed was air 2 L / min. When the power generation was 2 W, the methane conversion rate was 22.74%, the ethylene + ethane selectivity was 35.79%, and the rest was CO or CO2.

[0069] Example 5

[0070] The LSCF / GDC composite anode material in Example 3 was used to construct a button cell and a fuel cell stack, respectively, and their methane oxidative coupling reaction performance was investigated.

[0071] The button cell test temperature was 850°C, the anode feed was 20% CH4-80% N2, the flow rate was 50 mL / min, and the cathode feed was air, the flow rate was 500 mL / min. At an output power of 0.05 W, the methane conversion rate was 21.4%, the ethylene selectivity was 24.2%, the ethane selectivity was 8.1%, and the remaining products were CO or CO2.

[0072] The fuel cell stack is a dual-cell stack, the electrolyte material is 95% YSZ-5% GDC, and the cathode material is LSCF. The total area of ​​a single cell is 81cm 2 , the effective current collecting area is 25cm 2 The test temperature was 830°C and the pressure was 1 atm. The anode feed was methane 50 mL / min, nitrogen 200 mL / min, and the cathode feed was air 2 L / min. When the power generation was 4 W, the methane conversion rate was 32.56%, the ethylene + ethane selectivity was 36.47%, and the rest was CO or CO2.

[0073] Example 6: Preparation of LSCM / ScSZ composite anode material

[0074] Weigh 21.621g Mn(NO3)2·4H2O, 9.617g Na2WO4·2H2O, 4.329g Ce(NO3)3·6H2O and dissolve them in 150mL deionized water, and add 37g ScSZ powder under stirring. After continuous stirring and impregnation at room temperature for 6 hours, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6 hours. Then grind and sieve to less than 325 mesh to obtain a solid powder. Weigh 7.5g of the above powder, 2.5g LSCM powder (<325 mesh) and 10g V-006A solvent (the solvent required for making electrode materials, purchased from Heraeus), mix them evenly in an agate mortar to obtain LSM / YSZ composite anode material. The composition of the anode material is 2.7% CeO2-10.8% Mn2O3-13.5% Na2WO4-58.4% ScSZ-14.6% LSCM.

[0075] The composite anode material in Example 6 was used to construct a button battery and a fuel cell, respectively, and their methane oxidative coupling reaction performance was investigated.

[0076] The button cell test temperature is 850°C, the anode feed is 80% CH4-20% N2, the flow rate is 50mL / min, and the cathode feed is 15% O2-85% N2, the flow rate is 500mL / min. When the output power is 0.11W, the methane conversion rate is 32.2%, the ethylene selectivity is 21.7%, the ethane selectivity is 3.8%, and the remaining products are CO or CO2.

[0077] The fuel cell stack is a dual-cell stack, the electrolyte material is 80% YSZ-15% ScSZ-5% GDC, and the cathode material is LSCM. The total area of ​​a single cell is 81cm 2 , the effective current collecting area is 25cm 2 The test temperature was 900°C and the pressure was 1 atm. The anode feed was methane 160 mL / min and nitrogen 40 mL / min, and the cathode feed was oxygen 0.75 L / min and nitrogen 4.25 L / min. When the power generation was 2.8 W, the methane conversion rate was 18.7%, the ethylene + ethane selectivity was 28.22%, and the remaining products were CO or CO2.

[0078] At the same time, a similar method was used to prepare (LSM+LSCF) / (YSZ+ScSZ) composite anode materials, (LSCF+LSCM) / (ScSZ+GDC) composite anode materials, (LSM+LSCM) / (YSZ+GDC) composite anode materials and (LSM+LSCF+LSCM) / (YSZ+ScSZ+GDC) composite anode materials, and fuel cells were constructed with the above composite anode materials (the cathode materials were LSM cathode materials and LSCF cathode materials, respectively; the electrolyte materials were LSM, LSCF, LSCM, LSM / LSCF composite materials, LSCF / LSCM composite materials, LSM / LSCM composite materials and LSM / LSCF / LSCM composite materials, respectively), and their methane oxidative coupling reaction performance was investigated to be good.

[0079] Comparative Example 1: Preparation of YSZ composite anode material

[0080] Weigh 0.71g Mn(NO3)2·4H2O, 0.42g Na2WO4·2H2O, 1.15g Ce(NO3)3·6H2O and dissolve in 50mL deionized water, and add 4.0g YSZ powder under stirring. After continuous stirring and impregnation for 6 hours at room temperature, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6 hours. Then grind and sieve to less than 325 mesh. Weigh 4g of the above powder and 4g V-006A solvent in an agate mortar and mix evenly to obtain a YSZ composite anode material. The composition of the anode material is 9.0% CeO2-4.4% Mn2O3-7.4% Na2WO4-79.2% YSZ.

[0081] Comparative Example 2: Preparation of LSCF / GDC composite anode material (mixing ceramic solid materials first, then impregnating)

[0082] Weigh 4.104g Mn(NO3)2·4H2O, 2.529g Na2WO4·2H2O, 6.97g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water. Weigh 10g GDC powder and 34g LSCF powder, stir them evenly in agate grinding, and then pour them into the catalyst aqueous solution under stirring. After continuous stirring and impregnation for 6 hours at room temperature, slowly concentrate at 80℃ until the liquid is completely volatilized. The dried solid is transferred to a muffle furnace, heated to 850℃ and sintered in air for 6 hours. Then grind and sieve to less than 325 mesh. Weigh 10g of the above powder and mix it evenly with 10g V-006A solvent in an agate mortar to obtain LSCF / GDC composite anode material. The composition of the anode material is 5.5% CeO2-2.6% Mn2O3-4.5% Na2WO4-19.9% ​​GDC-67.5% LSCF.

[0083] Comparative Example 3:

[0084] A button cell was constructed using the YSZ composite anode material in Comparative Example 1, and its methane oxidative coupling reaction performance was investigated.

[0085] The button cell test temperature is 900°C, the anode feed is 20% CH4-80% N2, the flow rate is 50mL / min, and the cathode feed is air, the flow rate is 500mL / min. When the output power is -1.2W (i.e., additional electrical energy), the methane conversion rate is 26.8%, the ethylene selectivity is 18.3%, the ethane selectivity is 3.1%, and the remaining products are CO or CO2.

[0086] Since the YSZ composite anode material in Comparative Example 1 does not contain conductive substances, the internal resistance of the button battery constructed therefrom is relatively large, and the electromotive force of the chemical reaction of the reactants on both sides of the battery alone cannot provide a sufficiently large current (or oxygen flux). In order to achieve sufficient oxygen flux, additional electrical energy must be added.

[0087] Comparative Example 4:

[0088] A button cell was constructed using the LSCF / GDC composite anode material in Comparative Example 2, and its methane oxidative coupling reaction performance was investigated.

[0089] The button cell test temperature is 850°C, the anode feed is 20% CH4-80% N2, the flow rate is 50mL / min, and the cathode feed is air, the flow rate is 500mL / min. When the output power is -0.7W (i.e., additional electrical energy), the methane conversion rate is 15.2%, the ethylene selectivity is 21.3%, the ethane selectivity is 5.6%, and the remaining products are CO or CO2.

[0090] The LSCF / GDC composite material prepared by the method in Comparative Example 2 is prepared by first mixing LSCF powder with GDC powder and then compounding with the catalyst. This synthesis sequence results in a large amount of insulating catalyst material being deposited on the surface of LSCF, which affects the conductivity of LSCF and even the entire anode material, thereby increasing the overall internal resistance of the battery. Additional electrical energy is required to achieve sufficient oxygen flux.

[0091] Comparative Example 5:

[0092] The Ni|YSZ|LSM full cells purchased directly from Sofo were assembled into a dual-cell stack, that is, a fuel cell stack was constructed using traditional nickel-containing anodes, and its methane oxidative coupling reaction performance was examined.

[0093] The fuel cell stack is a dual-cell stack, the electrolyte material is YSZ, and the cathode material is LSM. The total area of ​​a single cell is 81cm 2 , the effective current collecting area is 25cm 2 The test temperature was 800℃ and the pressure was 1atm. The anode feed was methane 100mL / min, nitrogen 200mL / min, and the cathode feed was air 2L / min. The system had severe carbon deposition, the gas phase methane conversion rate was 3.7%, the CO selectivity was 90.3%, the CO2 selectivity was 9.7%, and no low-carbon hydrocarbons were generated.

[0094] In batteries constructed with traditional metal-containing anode materials, methane is easily catalytically decomposed on the surface of nickel to form carbon black and hydrogen. Carbon black deposition causes the pores of the battery anode to be blocked, and further blocks the gas path of the fuel cell stack. At the same time, carbon black is not a good catalyst for the methane conversion reaction at a reaction temperature of 800°C, resulting in a significant decrease in the methane conversion rate.

[0095] It should be understood that the specific order or hierarchy of steps in the disclosed process is an example of an exemplary method. Based on design preferences, it should be understood that the specific order or hierarchy of steps in the process can be rearranged without departing from the scope of protection of the present disclosure. The attached method claims present the elements of the various steps in an exemplary order and are not intended to be limited to the specific order or hierarchy described.

[0096] In the above detailed description, various features are grouped together in a single embodiment to simplify the disclosure. This method of disclosure should not be interpreted as reflecting an intention that the embodiments of the claimed subject matter require more features than are clearly stated in each claim. On the contrary, as reflected in the appended claims, the invention is in a state of having less than all the features of the disclosed individual embodiments. Therefore, the appended claims are hereby expressly incorporated into the detailed description, with each claim standing on its own as a separate preferred embodiment of the invention.

[0097] The above description includes examples of one or more embodiments. Of course, it is impossible to describe all possible combinations of components or methods for the purpose of describing the above embodiments, but it should be recognized by those skilled in the art that the various embodiments may be further combined and arranged. Therefore, the embodiments described herein are intended to cover all such changes, modifications and variations that fall within the scope of protection of the appended claims. In addition, with respect to the term "comprising" used in the specification or claims, the word is covered in a manner similar to the term "including", just as "including," is explained as a transitional word in the claims. In addition, any term "or" used in the specification of the claims is intended to mean "non-exclusive or".

Claims

1. A fuel cell for converting methane into low-carbon hydrocarbons, characterized in that: The anode material of the fuel cell includes a methane oxidative coupling catalyst and an oxygen ion-electron mixed conductor material, wherein the oxygen ion-electron mixed conductor material includes a first component and a second component, wherein the first component is a mixture of one or more of LSM, LSCF and LSCM, and the second component is a mixture of one or more of YSZ, ScSZ and GDC; The fuel cell is used to convert methane into low-carbon hydrocarbons and generate electrical energy when the cathode feed stream is a first mixed gas containing oxygen and the anode feed stream is a second mixed gas containing methane.

2. The fuel cell according to claim 1, wherein: The anode material of the fuel cell is prepared by a solution impregnation method, wherein the precursor of the methane oxidative coupling catalyst is loaded on the powder of the second component and then mixed with the powder of the first component to prepare the anode material.

3. The fuel cell according to claim 1, wherein: The mass fraction of the first component in the oxygen ion-electron mixed conductor material is 20-80%.

4. The fuel cell according to claim 1, wherein: The electrolyte material of the fuel cell is a mixture of one or more of YSZ, ScSZ and GDC.

5. The fuel cell according to claim 1, wherein: The cathode material of the fuel cell is one of LSM, LSCF or LSCM.

6. The fuel cell according to claim 1, wherein: The methane oxidative coupling catalyst is a cerium-manganese-tungsten catalyst, and the cerium-manganese-tungsten catalyst is a mixture of CeO2, Mn2O3 and Na2WO4.

7. The fuel cell according to claim 1, wherein: The mass ratio of the methane oxidative coupling catalyst to the oxygen ion-electron mixed conductor material is 12:88 to 27:

73.

8. The fuel cell according to claim 1, wherein: The molar percentage of oxygen in the first mixed gas is not less than 15%; The molar percentage of methane in the second mixed gas is 20% to 80%.

9. The fuel cell according to any one of claims 1 to 8, characterized in that: The operating temperature of the fuel cell is 800-900°C.

10. A method for converting methane into light hydrocarbons, characterized in that: include: A first mixed gas containing oxygen is introduced into the cathode of the fuel cell according to any one of claims 1 to 9, and a second mixed gas containing methane is introduced into the anode of the fuel cell, and the methane in the second mixed gas is converted into low-carbon hydrocarbons by the fuel cell to generate electrical energy.